1972
DOI: 10.1128/jvi.10.6.1184-1198.1972
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Interferon Action: Inhibition of Viral Messenger Ribonucleic Acid Translation in L-Cell Extracts

Abstract: Encephalomyocarditis (EMC) virus ribonucleic acid (RNA) stimulated the incorporation of "4C-amino acids into polypeptides in cell-free systems using preincubated S10 extracts from L cells. Incorporation was linear for over 2 hr. Analysis of the tryptic peptides derived from the polypeptide products formed in response to EMC RNA showed them to be virus specific. The major product, a polypeptide of 140,000 in molecular weight, migrated on sodium dodecyl sulfate-polyacrylamide gels with one of the virus-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…(i) Infection-activation of antiviral action. Friedman et al (1972) found that viral mRNA translation was the same in cell-free extracts prepared from normal and interferon-treated cells; however, extracts prepared from vaccinia or EMC virusinfected interferon-treated cells would not translate viral messages, although polyuridylic acid translation was uninhibited. Kerr et al (1973Kerr et al ( , 1974b then concluded that interferon-induced antiviral action requires virus infection to activate translation inhibition.…”
Section: Inhibition Of Viral Message Translation In Cells Extensive mentioning
confidence: 93%
See 1 more Smart Citation
“…(i) Infection-activation of antiviral action. Friedman et al (1972) found that viral mRNA translation was the same in cell-free extracts prepared from normal and interferon-treated cells; however, extracts prepared from vaccinia or EMC virusinfected interferon-treated cells would not translate viral messages, although polyuridylic acid translation was uninhibited. Kerr et al (1973Kerr et al ( , 1974b then concluded that interferon-induced antiviral action requires virus infection to activate translation inhibition.…”
Section: Inhibition Of Viral Message Translation In Cells Extensive mentioning
confidence: 93%
“…With the advances of interferon purification techniques, recent studies have been performed with interferon preparations with high specific activities. Voluminous information on the ability of interferon to inhibit virus-specific protein synthesis (Joklik and Merigan, 1966;Salb, 1966, 1968;Carter and Levy, 1967a, b;Levy and Carter, 1968;Kerr et al, 1970;Kerr, 1971;Esteban and Metz, 1973;Metz and Esteban, 19;/2;Friedman, 1968;Friedman et al, 1972) indicates clearly that at least one of the mechanisms of interferon actions is at the translational level. Actions of interferon at the transcriptional level have also been reported, with inhibition of viral mRNA synthesis in polymerase-containing viruses (Marcus et al, 1971;Oxman and Levin, 1971;Bialy and Colby, 1972;Manders et al, 1972), perhaps through an inhibition of the viral polymerase function.…”
Section: Antiviral Mechanisms: Sites Of Interferon Actions Against VImentioning
confidence: 99%
“…Conceivably, the synthesis of non-infectious oncornaviruses is governed by an incorporated provirus, while infectious viruses are formed by repeated infectious cycles. Although the mechanism of interferon action is still a matter of conjecture (Marcus and Salb, 1966;Levy and Carter, 1968;Kerr, 1971; Marcus et al, 1971; Metz and Esteban, 1972;Bialy and Colby, 1972;Falcoff et al, 1972;Friedman et al, 1972;Gupta et al, 1974;Samuel and Joklik, 1974) it is generally accepted that interferon treatment inhibits the transcription or translation of exogenous viral genetic information to a greater extent than that of endogenous cellular information. In accordance with this concept, one might predict that the synthesis of provirusdirected virions would be relatively resistant to interferon.…”
mentioning
confidence: 99%
“…Furthermore, such tRNA inactivation was also dependent on preincubation of the cell extracts [381. Therefore, the relevance of the tRNA reversible inhibition is questionable since it develops during preparation of the cell-free system and, moreover, tRNA isolated from interferon-treated cells shows the same ability cells with interferon as a necessary step for the manifestation of the interferon-mediated inhibition of translation [47]. The translation of EMC RNA in cell-free systems from mouse L-cells is well studied [30, 351.…”
Section: A) Cell-free Systems From Interferon-treated Virus-infectedmentioning
confidence: 99%